Development of diagnostic kit for human oral squamous cell carcinoma / Kazi Ahsan Jamil … [et al.] - Jamil, Kazi Ahsan; Sulaiman, Fatimah Suriati; Khor, Goot Heah; Mohd Zain, Rosnah (Research Innovation Business Unit, 2014)
p53 gene mutations observed at about 50 to 60 % in oral squamous cell carcinoma (OSCC). Problem Statement: The common mutation sites of p53 gene are still in controversy. Different techniques give differ results and even using same technique the results are different. Recently, Multiplex Ligation-Probe Amplification (MLPA) has been shown to be reliable and efficient technique for the detection of mutation. This method was consistent with cytogenetic and FISH (Fluorescence in situ hybridization) methods.